If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7x + -76 = 38 + -6x Reorder the terms: -76 + 6x + 7x = 38 + -6x Combine like terms: 6x + 7x = 13x -76 + 13x = 38 + -6x Solving -76 + 13x = 38 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -76 + 13x + 6x = 38 + -6x + 6x Combine like terms: 13x + 6x = 19x -76 + 19x = 38 + -6x + 6x Combine like terms: -6x + 6x = 0 -76 + 19x = 38 + 0 -76 + 19x = 38 Add '76' to each side of the equation. -76 + 76 + 19x = 38 + 76 Combine like terms: -76 + 76 = 0 0 + 19x = 38 + 76 19x = 38 + 76 Combine like terms: 38 + 76 = 114 19x = 114 Divide each side by '19'. x = 6 Simplifying x = 6
| 0=12x-3y | | -38=5(x-7)-8x | | 15y^3-25y^2=0 | | 8=3+6 | | 7x-192=-3x+56 | | 2+y^3=-1 | | 5(1-7a)+6(1-2a)=11 | | 6y+9=3(2-d) | | -6(3x-2)=5 | | x-46=-63 | | 5y+3y-2y=48 | | 25=9x+5-5x | | 3(5x-3)-6x=3(3x+2) | | 72+40=36+x | | 21+25m=28+18m | | 3y-6=2x+4 | | 13-17+24= | | 36-(2x+4)=2(x+6)+x | | 10-2(y-7)=3y+9 | | 150+20x=60+38x | | 32+x=-15 | | -(p+1)+5(p+8)=47 | | X+1.7=1.7x+22.9 | | 5-3(4x+3)=2 | | -(-2n-4)=5(n+2) | | 36=-9(10+1) | | 23=14+4n | | 5y^2+14=14 | | -(7n+1)-5(n+7)=12 | | 12+1.5x=15+.5 | | (7t-2)-(-3t+1)=-3-9t | | 3.5-0.02x=1.46 |